1997
DOI: 10.1002/(sici)1099-1611(199703)6:1<35::aid-pon241>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Is the Wish to Participate in a Cancer Rehabilitation Program an Indicator of the Need? Comparisons of Participants and Non‐Participants in a Randomized Study

Abstract: SUMMARYIn parallel with a randomized study of the 'starting again' rehabilitation program for cancer patients, a group of 73 non-participants were monitored (another 20 patients declined monitoring). In comparison with participants (intervention + control), gender, diagnosis, and 10 out of 18 dependent measures differed significantly at baseline. The non-participants group included more men, mostly with cancer of the prostate and irrespective of gender, they showed lower problem levels than participants throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
3
23
1
Order By: Relevance
“…Berglund et al and Berglund (7,19) report similar results and found in their studies of a rehabilitation programme for cancer patients that those who wanted to participate reported more problems at baseline than the controls.…”
Section: Discussionsupporting
confidence: 55%
“…Berglund et al and Berglund (7,19) report similar results and found in their studies of a rehabilitation programme for cancer patients that those who wanted to participate reported more problems at baseline than the controls.…”
Section: Discussionsupporting
confidence: 55%
“…This pattern suggested that the differences in psychological variables were the result of participants’ awareness of their group assignment and their expectations about it. Conversely, results from another randomized trial of a cancer rehabilitation program that emphasized physical training, information, and coping skills did not find any evidence that potential reactions to being assigned to control groups influenced any of the outcome variables 22. In this trial, non-participants (who did agree to complete assessments) reported lower levels of most problems at baseline compared to participants, potentially indicating a reduced level of need for the intervention.…”
Section: Participant Disappointment Regarding Treatment Group Assignmentcontrasting
confidence: 63%
“…Although this compensatory behavior may reduce the likelihood of identifying a true intervention effect and cloud the results of the study 22, it is an understandable response on the part of participants. Furthermore, it may be viewed as unethical in some situations to try to prevent this type of help-seeking.…”
Section: Participant Disappointment Regarding Treatment Group Assignmentmentioning
confidence: 99%
“…There are some studies that compare support group participants and non-participants of support groups [33,34]. However, this is the first study to examine different factors in their interrelation, resulting in knowledge about the relative importance of different factors in the interest for and the use of prostate cancer social support groups.…”
Section: Discussionmentioning
confidence: 99%